(untitled) (Texas Journal of Medical Science, 2023)
The study of the statement of the hemostatic system and vascular endothelium was made in newborns with hypoxic lesions of the nervous system. Some indicators of hemostasis (PTT, APTT, TT and fibrinogen) were determined in cord blood, as well as endothelial dysfunction marker Endothelin-1. In newborns who underwent a chronic hypoxia, a statistically significant increase of the fibrinogen level and endothelin-1 were revealed in the umbilical cord blood. During hypoxic lesions of the nervous system in newborns the vascular endothelium primarily reacts, causing activation of hemostasis and cerebral blood flow disorders.